Biocontrol of basal stem rot pathogen Ganoderma boninense by Pseudomonas aeruginosa - Lim, Pei Hui; Gansau, Jualang Azlan; Chong, Khim Phin (Bangladesh Journal of Botany, 2019)
Ganoderma boninense is the major causal pathogens of Basal Stem Rot (BSR) of oil palm. Potential antagonists were isolated from soil samples and dual culture assays were carried out. Four types of bacteria isolates showed PIRG greater than 50% against G. boninense and the most potential bacteria was B6 (PIRG = 75.76%) and identified as Pseudomonas aeruginosa. The interaction between P. aeruginosa with G. boninense was observed under Scanning Electron Microscopy (SEM). Secondary metabolites of P. aeruginosa, were extracted using hexane, ethyl acetate and acetone. Ethyl acetate extract showed the highest inhibition towards G. boninense with Minimum Inhibitory Concentration (MIC) of 0.04 mg/ml. Identification of compounds from the extract was further carried out using Liquid Chromatography-Mass Spectrometry (LC-MS). The most potential antimicrobial compound which may contribute to the biocontrol activity detected in the crude extract was 3-demethylubiquinone-9. P. aeruginosa and 3-demethylubiquinone-9 may potential to be further study for control of G. boninense.